Pembubaran Ormas Anti Pancasila: Kajian Konstitusional, Pembatasan HAM dan Negara Hukum - Nur Kholis Majid (GLOBAL SCIENTS PUBLISHER, 2025)
The dissolution of Social Organizations (Ormas) considered to be in conflict with Pancasila has gained renewed momentum following the issuance of Perppu Number 2 of 2017, which was subsequently enacted into Law Number 16 of 2017. These regulatory changes eliminate judicial mechanisms and grant the government direct authority to revoke the legal entity status or registered certificate of social organizations. This article aims to analyze the legal framework, dissolution mechanisms, and their implications for citizens' constitutional rights and the rule of law. This research uses a normative legal research method with a statutory approach and a conceptual approach. The research findings indicate that the shift in the dissolution mechanism of social organizations from a judicial model to an administrative one poses three main problems: a weakening of the principle of due process of law, the potential for excessive restrictions on freedom of association, and the absence of standard parameters regarding the phrase